Emotional factor of competitive self-mobilization of professional rowers - Cheban, Yurii Volodymyrovych; Chebykin, Oleksiy Yakovych; Plokhikh, Viktor Volodymyrovych; Massanov, Anatolii Viktorovych (Insight: the psychological dimensions of society, 2020)
Based on the provisions of the differential emotions theory, psychology of attitude, self-regulation concepts, the authors study the influence of emotiogenic stimuli and stressors (emotional factor) on the competitive self-mobilization of professional rowers. The purpose of the research is to determine the forms and sources of competitive self-mobilization of professional rowers under the conditions of influence of emotiogenic stimuli. The following methods were used in the empirical part: natural experiment, questionnaire for the evaluation of the frequency of use of mental resources in the competitive practice (image constructs, verbal forms) and experience of support of emotiogenic stimuli of a situation; testing for the identification of the frequency of experience of basal emotions, the motivation for success, and emotional personality traits. According to experimental design, to identify the capacity to overcome fatigue, the study participants have been passing a control distance of 150 m before and after intense training. The participants were 41 professional rowers of whom 27 are National Team members. Results. It is established that positive emotions of joy and pleasure significantly prevail (Friedman test) over negative ones (χ2=79.823; df 4; p<.001) in the emotional state of athletes’ activities. The athletes’ motivation for success is associated with joy (Rs=.337; p=.031) and pleasure (Rs=.398; p=.010). Athletes feel especially vivid emotional support from relatives (χ2=45.343; df=4; p<.001). The verbal formulas are often used for self-mobilization. Among image constructs, athletes commonly apply preliminary self-identification with the Winner (χ2=69.676; df=5; p<.001). The use of an image of “powerful mechanism” is connected with the motivation for success (Rs=.521; p<.001) that contributes to the improvement of the overall performance of competitive self-mobilization of athletes. The research concludes about the need to study the joint influence of emotional factor and volitional powers of professional rowers on the competitive self-mobilization.